A Comparative Study of Modelling RC Slab Response to Blast Loading with Two Typical Concrete Material Models. Issue 3 (September 2013) - Xu, Jiaming; Lu, Yong
The soundness of numerical simulation for reinforced concrete structures under blast loading is closely related to the capacity of the concrete models in dealing with the nonlinear behaviour of the material under complex stress conditions. To understand more comprehensively the demands a rigorous simulation may impose on a modelling approach and thereby the needs for improvement in the model formulation, a comparative numerical simulation study has been conducted in which two representative concrete material models, namely KCC and CSC models in LS-DYNA, are employed to model a typical RC slab subjected to blast load. For such a classical modelling situation, the model with KCC concrete material tends to fail prematurely with a total global failure of the slab, which is not consistent either with the experimental observations or with the CSC modelling results. Extensive analysis of the failure processes reveals that the abnormal response in the KCC model is linked to the rapid descending of the material model behaviour towards an effectively zero stress state following a tension/shear controlled damage process, and the consequent diminish of the interaction capacity between the steel rebar and the surrounding concrete. The findings from this study point a direction in which certain rectification will need to be considered in order to ensure a reliable modelling outcome with the KCC type concrete models in simulating the response of RC structures, both globally and locally.